2004
DOI: 10.1089/153531404323143639
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Heat Stress and Stage of Lactation (Early versus Late) on Fecal Shedding ofE. coliO157:H7 andSalmonellain Dairy Cattle

Abstract: Mature, healthy lactating dairy cattle were sampled on two farms in the southwestern United States to examine the effects of heat stress (Experiment I) and stage of lactation (Experiment II) on the fecal shedding of E. coli O157:H7 and Salmonella. To examine the effects of heat stress, fecal samples were collected from 45 cows at 7:00 AM (coolest part of the day) and 5:00 PM (hottest part of the day) in August 2002 on a 250 cow dairy. The study was replicated one month later (n = 170 total samples). A temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 16 publications
0
25
1
Order By: Relevance
“…With regard to age at the time of calving, a German study found that animals undergoing first lactation had a higher risk of STEC shedding than older cows (44), while a longitudinal study in the United Kingdom reported the prevalence of STEC O157 to be the highest in cows 2 years of age, the typical age at first calving (43). Although the multitude of factors that could contribute to the association between lactation number and STEC are not completely understood, they could be related to stress and the energy requirements needed by cows in the first lactation (45), in addition to decreased immune function. A negative energy balance, which is common during the first lactation, has been suggested to alter the digestive microbiota composition (45), which could potentially favor STEC colonization and shedding.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…With regard to age at the time of calving, a German study found that animals undergoing first lactation had a higher risk of STEC shedding than older cows (44), while a longitudinal study in the United Kingdom reported the prevalence of STEC O157 to be the highest in cows 2 years of age, the typical age at first calving (43). Although the multitude of factors that could contribute to the association between lactation number and STEC are not completely understood, they could be related to stress and the energy requirements needed by cows in the first lactation (45), in addition to decreased immune function. A negative energy balance, which is common during the first lactation, has been suggested to alter the digestive microbiota composition (45), which could potentially favor STEC colonization and shedding.…”
Section: Discussionmentioning
confidence: 99%
“…Although the multitude of factors that could contribute to the association between lactation number and STEC are not completely understood, they could be related to stress and the energy requirements needed by cows in the first lactation (45), in addition to decreased immune function. A negative energy balance, which is common during the first lactation, has been suggested to alter the digestive microbiota composition (45), which could potentially favor STEC colonization and shedding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations